Characterization of the physical constitution and the plantar footprint in the skaters of 7 to 11 years of the club of skate shark skating (Original) (Revista científica Olimpia, 2022)
The main objective of this research work is to be a support material for coaches and future researchers since in it we can identify strategies and tools to strengthen sports practice, from this a pedagogical proposal based on the results and findings can be generated. found, for the development of specific competencies in sport, in order to provide coaches with various strategies that cover aspects of sports planning and didactic manuals, providing them with a range of tools that allow them to improve processes in the sports area. For this research, the population was made up of coaches, athletes and parents, with an intentional non-probabilistic sample that was represented by 1 sports club, 4 coaches and 22 athletes. This is a descriptive transectional research, according to the data obtained, it is established that the athletes of the sports club under study lack specific training in the area, affecting the processes that are carried out during the development of the trainings, in addition to this, not many participate in training spaces such as competencies that allow improving the strategies implemented in these processes. Therefore, it is considered that expertise and qualification in a specific area such as sports training in said sport is always necessary. Therefore, it is inferred, in the need to create a strategy to help improve the teaching of said sport for the integral development of the athlete.
Keywords: strategies, sport, teaching, coach